Hubungan Mutu Pelayanan Keperawatan dengan Tingkat Kepuasan Pasien di Ruang Asoka RSUD Dr. R. Koesma Tuban - Tiara Putri Ryandini; Lukman Hakim (Puslitbang Sinergis Asa Professional, 2019)
The lack of patient satisfaction is due to the increasing demands of the patient's needs, but this is not accompanied by improvements in nurses' actions. If the customer feels dissatisfied with a service provided, then that service can be ascertained to be ineffective and inefficient. This is especially important for public services. Providing services to the community as done by RSUD Dr. R. Koesma Tuban, needs to get attention, especially in the quality of services to suit the needs and expectations of the community. This study focuses on the quality of nursing services and the level of patient satisfaction in the Asoka Hospital Dr. R. Koesma Tuban. This study aims to determine the relationship between the quality of nursing services with the level of patient satisfaction in the Asoka Hospital Dr. R. Koesma Tuban. This study uses analytic survey research with cross sectional approach, while the data analysis used is the Spearman Rank correlation test. The population used in this study were patients in the Asoka room of RSUD dr. R. Koesma Tuban who fit the inclusion criteria as many as 155, with a large sample of 112 respondents using a simple random sampling technique. The results showed that most patients were quite satisfied with the quite good nursing services. Spearmen Correlation Test Results (rs) obtained, the variable quality of nursing services (p <0.05) has a relationship to the level of patient satisfaction with moderate correlation (r = 0.476) and the direction of the positive correlation which means the better the quality of nursing services, the higher the level of satisfaction patient.Almost half of the nurses at Asoka Room RSUD dr. R. Koesma Tuba have a good quality nursing service. Almost half of the patient at Asoka Room RSUD dr. R. Koesma Tuban feel satisfy with nurse’s service; there is a correlation between the quality of nurse service and the level of patient satisfaction at Asoka Room RSUD dr. R. Koesma Tuban.